Ritual Landscapes and Borders Within Rock Art Research : Papers in Honour of Professor Kalle Sognnes - Heidrun Stebergløkken; Ragnhild Berge; Eva Lindgaard (Archaeopress Archaeology, 2015)
Ritual landscapes and borders are recurring themes running through Professor Kalle Sognnes'long research career. This anthology contains 13 articles written by colleagues from his broad network in appreciation of his many contributions to the field of rock art research. The contributions discuss many different kinds of borders: those between landscapes, cultures, traditions, settlements, power relations, symbolism, research traditions, theory and methods. We are grateful to the Department of Historical studies, NTNU; the Faculty of Humanities; NTNU, The Royal Norwegian Society of Sciences and Letters and The Norwegian Archaeological Society (Norsk arkeologisk selskap) for funding this volume that will add new knowledge to the field and will be of importance to researchers and students of rock art in Scandinavia and abroad.